Developing Senior High School Student’s Chemical Literacy Skills Through Inquiry-Based Online Chemistry Learning - Elly Albert Zebua; Kelly Sinaga (Universitas Tadulako, 2021)
This paper is motivated by the challenges of chemistry class during the online learning period in developing students’ chemical literacy skills that were found during internship two by the author at a school in North Sulawesi at Senior High School. Based on these activities, it is known that the limitations of students in understanding chemical materials and concepts during online learning pose as a challenge for teachers to carry out the chemistry lessons long distanced. This paper aims to review the development of students’ literacy skills through inquiry-based learning. This paper also aims to examine the implications of chemical literacy in helping Christian teachers guide students to God's wisdom through inquiry-based chemistry’s online learning. The results from this study showed that the chemical literacy skills of students in the school where the author carried out field experience program two activities showed positive results; however, it was not comprehensive. Furthermore, chemical literacy helped Christian teachers observe students’ development in understanding chemical concepts and their relevance to biblical principles. This study concluded that honing chemical literacy skills through inquiry-based online learning can help students be more active in obtaining information. Good chemical literacy skills will help students make decisions based on problems that are always based on biblical principles. The author of this study suggests examining strategies in addition to inquiry-based learning, which can improve student’s chemical literacy skills, especially in online chemistry learning.